Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1999
DOI: 10.1115/99-gt-152
|View full text |Cite
|
Sign up to set email alerts
|

On the Development and Application of the FRAP® (Fast-Response Aerodynamic Probe) System for Turbomachines: Part 1 — The Measurement System

Abstract: Ill I II I 111111111 HM I • ABSTRACTThis contribution gives an overview of the current state, performance and limitations of the fast-response aerodynamic probe measurement system (MAP* System) developed at the Turbomachinery Lab of the ETH Zurich. In particular, the following topics are addressed:Probe technology: Miniature probes with tip diameter ranging from 0.84 to 1.80 mm (1-sensor and 3-sensor probes respectively) have been developed. New technologies derived from microelectronics and micromechanics hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The FRAPP concept comes from the combination of fast-response pressure transducers, typically of the piezoresistive kind, with aerodynamic directional pressure probes. The transducers can be flush-mounted on the probe head [14], enhancing the frequency response despite fragility; in other examples [6,[15][16][17], the researchers preferred to embed the transducers within the probe head to enhance the probe strength. Excellent reviews on the early stages of FRAPP development can be found in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The FRAPP concept comes from the combination of fast-response pressure transducers, typically of the piezoresistive kind, with aerodynamic directional pressure probes. The transducers can be flush-mounted on the probe head [14], enhancing the frequency response despite fragility; in other examples [6,[15][16][17], the researchers preferred to embed the transducers within the probe head to enhance the probe strength. Excellent reviews on the early stages of FRAPP development can be found in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…All these issues have been addressed both experimentally and by proper CFD simulations; experiments require high promptness instrumentation like FRAPP (among others [29][30][31][32]) or LDV and PIV. Simulation, as well, requires high performance codes and schemes able to face the sliding of rotors with respect to the stationary components.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by using the FRAP-HTH with the sampling frequency of 200 kHz, approximately 16 and 21 measured data can be acquired in one pitch downstream from the L-1 and L-0 stages, respectively, when a moving blade passes the fixed traversing position. The design and operation of the current fast-response aerodynamic probes are based on the developments made over the past two decades at the Laboratory for Energy Conversion at ETH Zürich [10][11][12]. The newly developed FRAP-HTH has some similarities to the probe developed by Lenherr et al [11].…”
Section: Experimental Facilitymentioning
confidence: 99%